Analisis Penerapan Kepemimpinan Kepala Madrasah Terintegrasi Nilai-Nilai Religius di Daerah Istimewa Yogyakarta - Bowo, Ahmad Nasir Ari; Rahman, Ahmad Syafii; Rahayu, Supriati Hardi; Musaadah, Alfi Mamla’atul; Ibrohim, Busthomi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The background of this research is learning problems, low teacher performance, character, work programs are not implemented properly due to the less than optimal leadership of the principal. The formulation of the problem in this study is how is the leadership of the islamic schools head integrated with religious values? The purpose of this research is to describe and find the leadership of principals who are integrated with religious values. This study uses a qualitative method of multiple case study types. The research locations were Madrasah Aliyah Madania and Salaffiyah Islamic Boarding School Fadlun Minalloh D.I. Yogyakarta. Data sources include: Headmaster, Madrasah, Deputy Headmaster, and Teachers. Data collection techniques include: in-depth interviews, observation, and documentation studies. The results: the application of integrated leadership to religious values includes: Deliberation, effective communication, collaboration, cooperation, honesty, responsibility, trustworthiness, strategic thinking. Headmaster need to implement planning, organizing, implementing and monitoring.